2006
DOI: 10.1002/dmrr.706
|View full text |Cite
|
Sign up to set email alerts
|

Economic aspects of diabetic foot care in a multidisciplinary setting: a review

Abstract: Diabetic foot problems are frequent and are associated with high costs. A multidisciplinary approach to diabetic foot problems has proved to be cost saving with regard to cost of treatment itself. Nevertheless, it remained unclear if these savings could offset the overall costs involved in implementing this kind of approach. The few studies that address this issue specifically all show an acceptable cost-effectiveness, but often the profit will be evident after some years only, because long-term costs are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 45 publications
0
37
0
3
Order By: Relevance
“…Third, even though the costs of footwear and offloading devices are often considered to be substantial, it is important that such costs are viewed in relation to the total cost of care for a foot ulcer and the inherent increased risk of amputation. Although the direct costs of a foot ulcer have been estimated to be substantial, the question of cost effectiveness of the various treatments still remains to be determined [116]. Fourth, a major obstacle to comparison of studies is the lack of standardization in terminology, prescription, manufacture, and material properties of footwear and offloading devices.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Third, even though the costs of footwear and offloading devices are often considered to be substantial, it is important that such costs are viewed in relation to the total cost of care for a foot ulcer and the inherent increased risk of amputation. Although the direct costs of a foot ulcer have been estimated to be substantial, the question of cost effectiveness of the various treatments still remains to be determined [116]. Fourth, a major obstacle to comparison of studies is the lack of standardization in terminology, prescription, manufacture, and material properties of footwear and offloading devices.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Several retrospective single-centre studies, using different methodologies, have found that costs for foot ulcer treatment in general are also high [7][8][9][10]. The pathophysiology of diabetic foot disease is complex, and because several factors may play a role in the development of foot ulcers, the population of individuals presenting with diabetic foot ulcers is relatively heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Treatment of diabetic foot complications is a major financial burden on the healthcare system. [7][8] Foot ulcers are, in most cases, caused by a combination of risk factors associated with chronic complications of diabetes. 9,10 These include long-term hyperglycaemia, which can lead to microvascular disease that damages the small blood vessels and causes malfunctioning of the nerves.…”
Section: Introductionmentioning
confidence: 99%